2023
DOI: 10.1007/s11673-023-10261-8
|View full text |Cite
|
Sign up to set email alerts
|

Navigating the Ethical and Methodological Dimensions of a Farm Safety Photovoice Project

Abstract: Scholars have noted persistent high rates of agricultural health and safety incidents and the need to develop more effective interventions. Participatory research provides an avenue to broaden the prevailing research paradigms and approaches by allowing those most impacted to illuminate and work to solve those aspects of their lives. One such approach is photovoice, an emancipatory visual narrative approach. Yet, despite its broad appeal, photovoice can be hard to implement. In this article, we leverage our ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 79 publications
0
0
0
Order By: Relevance
“…There already exists extensive guidance on photovoice, including step-by-step planning of a photovoice activity, debriefing picture taking, ensuring participants' privacy and physical safety, and ensuring photo rights (Evans et al, 2022;Jongeling et al, 2016;Wang & Redwood-Jones, 2001). Still, scholars have noted that practical guidance is needed to help researchers develop a photovoice project, particularly to allow researchers' adherence with the principles of both photovoice and human subject reviews (Lenette et al, 2018;Teti, 2019;Yanar et al, 2016;Becot et al, 2023). Furthermore, every photovoice project generates a unique set of situational ethical and methodological dilemmas for both the participants and those initiating the activity (Lenette et al, 2018;McDonald & Capous-Desyllas, 2021).…”
Section: Why Use Photovoice As a Tool For Engaging With Food Service ...mentioning
confidence: 99%
See 1 more Smart Citation
“…There already exists extensive guidance on photovoice, including step-by-step planning of a photovoice activity, debriefing picture taking, ensuring participants' privacy and physical safety, and ensuring photo rights (Evans et al, 2022;Jongeling et al, 2016;Wang & Redwood-Jones, 2001). Still, scholars have noted that practical guidance is needed to help researchers develop a photovoice project, particularly to allow researchers' adherence with the principles of both photovoice and human subject reviews (Lenette et al, 2018;Teti, 2019;Yanar et al, 2016;Becot et al, 2023). Furthermore, every photovoice project generates a unique set of situational ethical and methodological dilemmas for both the participants and those initiating the activity (Lenette et al, 2018;McDonald & Capous-Desyllas, 2021).…”
Section: Why Use Photovoice As a Tool For Engaging With Food Service ...mentioning
confidence: 99%
“…Unique considerations associated with picture taking and sharing must be made. Organizers of a photovoice project need to consider, among many things, the safety of participants when taking pictures, the consent process to take pictures of other people, especially if minors are involved; picture rights and ownership; and possible negative judg-ments made about participants or their community (Sutton-Brown, 2014;Becot et al 2023). In designing and implementing this project, we found that there are unique challenges particular to the school setting, where minors are present, that are not described in existing published photovoice resources.…”
Section: Why Use Photovoice As a Tool For Engaging With Food Service ...mentioning
confidence: 99%
“…There already exists extensive guidance on photovoice, including step-by-step planning of a photovoice activity, debriefing picture taking, ensuring participants' privacy and physical safety, and ensuring photo rights (Evans et al, 2022;Jongeling et al, 2016;Wang & Redwood-Jones, 2001). Still, scholars have noted that practical guidance is needed to help researchers develop a photovoice project, particularly to allow researchers' adherence with the principles of both photovoice and human subject reviews (Lenette et al, 2018;Teti, 2019;Yanar et al, 2016;Becot et al, 2023). Furthermore, every photovoice project generates a unique set of situational ethical and methodological dilemmas for both the participants and those initiating the activity (Lenette et al, 2018;McDonald & Capous-Desyllas, 2021).…”
Section: Why Use Photovoice As a Tool For Engaging With Food Service ...mentioning
confidence: 99%
“…Unique considerations associated with picture taking and sharing must be made. Organizers of a photovoice project need to consider, among many things, the safety of participants when taking pictures, the consent process to take pictures of other people, especially if minors are involved; picture rights and ownership; and possible negative judg-ments made about participants or their community (Sutton-Brown, 2014;Becot et al 2023). In designing and implementing this project, we found that there are unique challenges particular to the school setting, where minors are present, that are not described in existing published photovoice resources.…”
Section: Why Use Photovoice As a Tool For Engaging With Food Service ...mentioning
confidence: 99%